EXPERIMENTAL STUDY ON FIBER REINFORCED SELF COMPACTING CONCRETE - Mr. B. M Malagimani; Dr. M. G. Deshmukh; Gosavi Shriyash, Gavali Sujit Masal Vivek, Adamane Saurabh, Bhange Suraj, Namade Soham, Aldar Shankar (International Journal of Innovations in Engineering Research and Technology, 2022)
The usefulness of fiber reinforced concrete (FRC) in various civil engineering applications is indisputable. Fiber reinforced concrete has so far been successfully used in slabs on grade, architectural panels, precast products, offshore structures, structures in seismic regions, thin and thick repairs, crash barriers, footings, hydraulic structures and many other applications. Fiber Reinforced Concrete (FRC) is gaining attention as an effective way to improve the performance of concrete. Fibers are currently being specified in tunneling, bridge decks, pavements, loading docks, thin unbonded overlays, concrete pads, and concretes slabs. These applications of fiber reinforced concrete are becoming increasingly popular and are exhibiting excellent performance. Fiber-reinforced concrete (FRC) is concrete containing fibrous material which increases its structural integrity. It contains short discrete fibers that are uniformly distributed and randomly oriented. Fibers include steel fibers, glass fibers, synthetic fibers and natural fibers. This study presents understanding strength of fiber reinforced concrete.